LANGUAGE ART IN "FAIDUBBORSINSEANG" NOVEL OF S. SINONTHONG - SYVONGSAK, Somthapheuy (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This article is to investigate S. Sinonthong’s composition art in the novel of “Faidubborsinseang”. A qualitative approach is applied to achieve the objective, thecomposition art of the usage of image language in an article which is based on the theories of ViphaKongkanun. The method is analysis, explanation, interpretation, and evaluation. Regarding the application of image language, it found that the application of image language consists of 86 expressions which include 13 types as metaphor expressions, simile expressions, synecdoche expressions, metonymy expressions, oxymoron expressions, paradox expressions, synesthesia expressions, hyperbole expressions, overstatement expressions, allusion expressions, personification expressions, analogy expressions, rhetorical question expressions. The image language can reflect on language users’ imagination which demonstrates through transferring process of the original meaning of the image to a new meaning in comparative form. In addition, it is discovered that the image language of the Lao novel has foundation from human experiences such as thoughts, society, and culture - people, animals, objects, and nature.